2009
DOI: 10.2337/dc09-1635
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Childhood Glucose Homeostasis Variables in Predicting Adult Diabetes and Related Cardiometabolic Risk Factors

Abstract: OBJECTIVEThis study examines the usefulness of childhood glucose homeostasis variables (glucose, insulin, and insulin resistance index [homeostasis model assessment of insulin resistance {HOMA-IR}]) in predicting pre-diabetes and type 2 diabetes and related cardiometabolic risk factors in adulthood.RESEARCH DESIGN AND METHODSThis retrospective cohort study consisted of normoglycemic (n = 1,058), pre-diabetic (n = 37), and type 2 diabetic (n = 25) adults aged 19–39 years who were followed on average for 17 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 25 publications
3
68
1
Order By: Relevance
“…In addition, the Bogalusa Heart Study has recently confirmed that adiposity and HOMA-IR are interrelated. 21 Programs that include increased activity and behavior modification have traditionally resulted in more improvements in childhood obesity. 6 During the development of the program, the major goal was to provide the child and parent with tools to empower them to make better decisions that would promote a healthier lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Bogalusa Heart Study has recently confirmed that adiposity and HOMA-IR are interrelated. 21 Programs that include increased activity and behavior modification have traditionally resulted in more improvements in childhood obesity. 6 During the development of the program, the major goal was to provide the child and parent with tools to empower them to make better decisions that would promote a healthier lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…140,141 In particular, severe obesity in childhood is strongly associated with future development of T2DM. 81,138,[142][143][144][145][146][147][148] In one study, severe obesity at baseline was an independent predictor of eventual development of T2DM. 81 Adiposity in childhood is also known to predict intermediate cardiovascular outcomes in adulthood, including noninvasive measures of target-organ damage.…”
Section: Long-term Risksmentioning
confidence: 99%
“…32 Three major studies have previously examined the association between insulin levels in childhood and later T2DM. Nguyen et al 33 showed that children in the top decile for insulin were .5 times more likely to develop T2DM than those with a lower insulin value in 1120 participants of the Bogalusa Heart Study, whereas Morrison et al 34 demonstrated among 556 North American schoolgirls that fasting insulin concentrations at age 10 predicted T2DM at a mean age of 24 years. However, both studies were biracial and had few participants with T2DM in adult life (n = 25 and 11, respectively).…”
Section: Discussionmentioning
confidence: 99%